2014
DOI: 10.1103/physreve.89.062905
|View full text |Cite
|
Sign up to set email alerts
|

Thermal enhancement and stochastic resonance of polaron ratchets

Abstract: . (2014) 'Thermal enhancement and stochastic resonance of polaron ratchet.', Physical review E., 89 (6). 062905.Further information on publisher's website:http://dx.doi.org/10.1103/PhysRevE.89.062905Publisher's copyright statement:Reprinted with permission from the American Physical Society: L. S. Brizhik, A. A. Eremko, B. M. A. G. Piette, and W. J. Zakrzewski, Physical Review E, 89, 062905, 2014. c 2014 by the American Physical Society. Readers may view, browse, and/or download material for temporary copying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Moreover, this is in the case of the symmetric Peierls-Nabarro potential (36). Indeed, the numerical simulations of the discrete set of Equations (29) has demonstrated the existence of the stochastic resonance of a soliton drift in the oscillating electrical field, subjected to thermal noise (Brizhik et al, 2014). In Figure 6, we show the amplitude of such drift (number of cites per period of the field) as a function of the temperature for two values of the period of the field, T e ¼ 120 and T e ¼ 150.…”
Section: Stochastic Resonance Of Solitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this is in the case of the symmetric Peierls-Nabarro potential (36). Indeed, the numerical simulations of the discrete set of Equations (29) has demonstrated the existence of the stochastic resonance of a soliton drift in the oscillating electrical field, subjected to thermal noise (Brizhik et al, 2014). In Figure 6, we show the amplitude of such drift (number of cites per period of the field) as a function of the temperature for two values of the period of the field, T e ¼ 120 and T e ¼ 150.…”
Section: Stochastic Resonance Of Solitonsmentioning
confidence: 99%
“…The detailed numerical study of this phenomenon is done in Brizhik et al (2014). As an example, let us consider a chain with a lattice unit cell, in which only the electron-lattice coupling constants of two types of atoms are different, and elasticity constants and electron resonant constants, are respectively, equal, so that d ¼ 0, w ¼ 0.…”
Section: Stochastic Resonance Of Solitonsmentioning
confidence: 99%
“…Here, we consider the so-called zero temperature regime [54,55], in which thermal effects are negligible. Thus, we can better understand the true role of the carrier-lattice coupling and the superposed electric fields in polaron dynamics and stability.…”
Section: Model and Formalismmentioning
confidence: 99%
“…Thus, we can better understand the true role of the carrier-lattice coupling and the superposed electric fields in polaron dynamics and stability. In a next study, thermal effects can be explored by using a white stochastic signal as the fluctuation term and Langevin formalism [34,55]. The above set of differential equations was solved by using a standard Runge-Kutta method with a time step that is small enough to keep the wave function norm conservation…”
Section: Model and Formalismmentioning
confidence: 99%
“…Studies of polaron transport on α helical polymers have recently been reported by Henning [9][10][11][12]. However, in most of these studies the polaron is "kicked" from its rest state via a perturbation [13].…”
mentioning
confidence: 99%